Implementasi Manajemen Risiko Dalam Meningkatkan Kemampuan IT Siswa - Wahyudi, Riki; Hidayat, Wahyu (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
This study looks at risk management as a concept and how it is used, especially in education (schools). The examination directed talks about the utilization of hazard the executives in further developing understudies' IT abilities at SMPN 1 Baleendah. The research method taken is qualitative because the data collection process is made using interviews, observation, and data analysis. This plans to decide the viability of the execution in the educating and growing experience in the homeroom utilizing data innovation, likewise to figure out the supporting and hindering elements over learning, and to figure out the effect that could happen on the educational experience, so later an assessment will be completed so the educational experience is better continue. Because in improving the quality of education in this modern era, it is very important to pay attention to the use of technology that makes learning programs and the school development process easier. and it is hoped that this research can become an illustration and direction for other schools in general to improve the quality of their education. The results of this study are in order to calculate and assess how effective the use of IT in SMPN 1 Baleendah.